Pathological altruism - Oakley, Barbara A., 1955- (New York : Oxford University Press, 2011)
'Pathological Altruism' is a groundbreaking new book - the first to explore the negative aspects of altruism and empathy seemingly uniformly positive traits. In fact, pathological altruism, in the form of an unhealthy focus on others to the detriment of one's own needs, may underpin some personality disorders.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 17, 2012).
Includes bibliographical references and index.
Keywords: Altruism